ANALISIS BEBAN KOGNITIF DAN KONSTRUKTIVISME DALAM PEMBELAJARAN IPA MENGGUNAKAN MEDIA PPT DI KELAS VII SMP NEGERI 40 SERAM BAGIAN TIMUR - Wirda Wiwik La Otje; Farida Febriati (STKIP Subang, 2026)
This study aims to analyze cognitive load and constructivism in science learning using PowerPoint (PPT) media among seventh-grade students at SMP Negeri 40 Seram Bagian Timur. This study is motivated by the dominant use of presentation media that focuses on delivering information rapidly and densely without considering students’ information processing capacity and the lack of student-centered learning practices. This condition causes students difficulties in understanding the material, losing focus, becoming passive during learning activities, and showing low learning engagement throughout the learning process.This study employed a qualitative descriptive approach with a case study design. Observations were conducted during two science learning sessions focusing on teacher activities, student responses, the use of digital learning media, classroom interaction, and students’ constructivist learning activities. Data collection techniques included observation, interviews, and documentation. Data were analyzed using Cognitive Load Theory, Multimedia Learning Theory, and constructivist theory perspectives.The findings reveal that the use of PPT media containing excessive text, minimal visualization, and rapid explanations creates relatively high extraneous cognitive load among students. This condition is reflected in students experiencing confusion in understanding science concepts, difficulties following teachers’ explanations, and focusing more on taking notes rather than constructing conceptual understanding. Furthermore, the use of PPT media that still tends to reinforce teacher-centered learning causes classroom interaction to become less constructivist. Students were less active in discussions, showed minimal collaborative learning, and received limited scaffolding in constructing conceptual understanding.This study recommends the use of PPT media designed with segmenting, signaling, visual simplification, and constructivist learning approaches through interactive discussion, collaborative learning, and student-centered learning to reduce students’ cognitive load and improve learning engagement. The development of educational technology-based learning media that considers students’ working memory capacity and knowledge construction activities is expected to create more effective, interactive, and meaningful science learning.